PENTINGNYA PENDIDIKAN AQIDAH AKHLAK BAGI SISWA KELAS V MADRASAH IBTIDAIYAH NURUL HIKMAH HAURGEULIS INDRAMAYU TAHUN 2019 - Tardi Tardi; Abdur Rahim (Bajang Institute, 2022)
Education in Indonesia is currently faced with an unfavorable situation. This problem appears marked by various phenomena of Indonesian people's life which show the weakening of the nation's character and culture which is believed to have been deeply rooted. With regard to education, the collapse of the mentality of the nation's children that can be witnessed today is believed to be the result of an education pattern that ignores the development of the nation's character and culture and the basic values of the state. The author argues that moral aqidah education which is part of Islamic religious education which contains character values, can answer the problem of the weak character of the Indonesian nation by understanding the basic values of the country through moral aqidah education. The purpose of this study was to explain the importance of moral aqidah education in fifth grade students of Madrasah Ibtidaiyah Nurul Hikmah Haurgeulis, Indramayu. This study is a qualitative research, data collection techniques by means of observation, interviews, and documentation, the data sources in this study are primary data and secondary data. The results of the study show that the importance of moral aqidah education in fifth grade (five) students of Madrasah Ibtidaiyah Nurul Hikmah Haurgeulis, Indramayu that, (1) To strengthen children's belief that Allah is the only God who created nature, so that he/she avoids shirk, (2 ) So that children know the nature of their existence as human beings, and (3) Print children's behavior into Islamic behavior with noble character.